INTERPRETASI MUSIKAL DALAM ARANSEMEN PADUAN SUARA LAGU “TAK KU TAHU KAN HARI ESOK” KARYA IRA FOREST STANPHILL - Risna Rante Sampe; Nikodemus; Michael Adrianto; Leny Febrianti Daniel (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This research aims to describe the arrangement process and analyze the structural form of the arrangement of the sacred song “I Don’t Know About Tomorrow” by Ira F. Stanphill in a four-part choir format. This song is widely known among Protestant churches for its strong message of faith and hope; however, in the version of the Supplement to the Church Hymnal (PKJ), it is considered less expressive and musically monotonous. This study employs a qualitative approach with descriptive-analytical methods and a practice-based reflective approach. The arrangement process is carried out through five stages: concept formulation, initial arrangement creation, idea development, further composition, and final revision. The arrangement results showcase musical richness through the application of reharmonization techniques (simple substitutions and ii–V progressions), melodic variations (fillers, counter-melodies, pads, drones), the use of musical textures (monophony, homophony, homorhythm), and motif development (repetition and sequence). The structure of the arrangement work has an AB–A’B form with additional sections for intro, interlude, and ending. This research not only produces a musical work that can be used in church services but also contributes academically to the development of vocal music arrangement theory.